Rancangan Bangun Sistem Informasi Perpustakaan Berbasis Web Menggunakan Model Waterfall - Yulianti, Yulianti; Biantoro, Anif; Adi, Geri Santoso; Asshidiqie, Muhammad; Putra, Rizky Abiansyah; Saifudin, Aries (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2022)
This research describes implementation of information technology in  elementary school library. library strategy utilizes an electronic technique that isn't yet incorporated, and the information handling utilizes MS Office to store understudy information, really take a look at exchange information, and bring books back. Hence, schools need a structure that can address every one of the issues of the library. The executives of data frameworks can foster frameworks utilizing site based data innovation with a cascade model and MySQL data set. The reason for making library applications is to give ideal help, so the put away information is more exact and staff can undoubtedly find information that is coordinated into the library application framework.